Dissecting gene regulatory networks governing human cortical cell fate - Jingwen W. Ding; Chang N. Kim; Megan S. Ostrowski; Yashodara Abeykoon; Bryan J. Pavlovic; Jenelle L. Wallace; Nathan K. Schaefer; Tomasz J. Nowakowski; Alex A. Pollen (Nature, 2026)
Abstract Human cortical neurogenesis involves conserved and specialized developmental processes during a restricted window of prenatal development. Radial glia (RG) neural stem cells shape cortical cell diversity by giving rise to excitatory neurons, oligodendrocytes and astrocytes, as well as olfactory bulb interneurons (INs) and a recently characterized population of cortical INs 1,2 . Complex genetic programs orchestrated by transcription factor (TF) circuits govern the balance between self-renewal and differentiation, and between different cell fates 3–8 . Despite progress in measuring gene regulatory network activity during human cortical development 9–12 , functional studies are required to evaluate the roles of TFs and effector genes in human RG lineage progression. Here we establish a human primary culture system that allows sensitive discrimination of cell fate dynamics and apply single-cell CRISPR interference (CRISPRi) screening 13,14 to examine the transcriptional and cell fate consequences of 44 TFs active during cortical neurogenesis. We identified several TFs with new roles in cortical neurogenesis, including ZNF219 —previously uncharacterized—that represses neural differentiation and NR2E1 and ARX that have opposing roles in regulating RG lineage plasticity and progression across developmental stages. We also detected convergent effector genes downstream of multiple TFs enriched in neurodevelopmental and neuropsychiatric disorders and observed conserved mechanisms of RG lineage plasticity across primates. We further uncovered a post-mitotic role for ARX in safeguarding IN subtype specification through repressing LMO1 . Our study provides a framework for dissecting regulatory networks driving cell fate consequences during human neurogenesis.